The kaleidoscope of lived curricula : learning through a confluence of crises : 13th annual Curriculum & Pedagogy Group 2021 edited collection - Lewis, Karin Ann; Banda, Kimberly; Briseno, Martha; Weber, Eric J. (Curriculum and pedagogy series., 2021)
"Within the context of recent, and ongoing, plural pandemics such as COVID-19 up/ending lives, social and racial chaos and catastrophe, political pressures, and economic convulsions, The Kaleidoscope of Lived Curricula: Learning Through a Confluence of Crises offers a journey through a collection of scholarly reflective creative pieces--stories of lived curricula. Like a kaleidoscope filled with loose pieces of simple colored glass and objects transforming into an infinite variety of beautiful forms and patterns with the slightest turn, the collection of pieces in this book reflect images of the sky that nurtures life; sun that illuminates understanding; earth that shifts and grounds us; fire that is primal, intending to spark and extend curricular and pedagogical conversations and understandings. This book provides a lens through which to observe and experience how plural pandemics shifted the lived curricula--the colored glass and objects in the lives of others--to surface, contextualize, confront, and curate challenges, as well as celebrate the courageous and elevate and empower marginalized groups to relate, learn, and heal through stories of lived curricula. This beautiful collection brings readers to an awareness, understanding, and appreciation of the lived curricula unlike they have ever experienced before"--